PENINGKATAN HASIL BELAJAR GEOGRAFI MATERI ATMOSFER DENGAN MENGGUNAKAN APLIKASI MEDIA PEMBELAJARAN DIGITAL (MPD) BAGI SISWA KELAS X.2 SMA NEGERI I GROBOGAN PADA SEMESTER 2 TAHUN 2009-2010 - Supriyadi, Aris (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2014)
This study aimed to improve learning outcomes in geography atmosphericmaterial using Digital Learning Media application (MPD) for Students X.2 SMA1 Grobogan the Year 2009/2010 Semester 2 (first grade of Senior High SchoolStudents). Sources of data in this study consisted of: (1) The results of the abilityevaluation to analyze the geosphere elements before action; (2) The results of theability evaluation to analyze the geosphere elements after the action (in the formof test scores). The results of this study showed that by using the Learning DigitalMedia Applications (MPD) can improve learning outcomes for students ofGeography Matter Atmospheric X.2 SMA 1 Grobogan in the 2nd half year2009/2010. Interpretation of these results are based on research result in the firstcycle and the second cycle compared with the pre-cycle conditions, i.e. there is adifference or learning outcomes improvement. Quite category student grades (62-75) decreased by 60% in the first cycle and 70% in the second cycle. A decreasein â€œFairâ€ category (62-75) this resulted in increasement of â€œGoodâ€ category(76-89) that was equal to 60% in the first cycle and 70% in the second cycle andthe increasement of the â€œExcellentâ€ category (90-100) by 4%.